The Role of the Ultrasonographic Knee Assessment in the Diagnosis of Patellofemoral Pain Syndrome: - Ghasemi , Nasim; Haghighat, Shila; Karami, Mehdi; Vahdatpour, Babak; Soleimany , Samira (Galen Medical Journal, 2022)
Background: Patellofemoral Pain Syndrome (PFPS) is a common anterior knee compartment pain etiology. It has been aimed to assess the ultrasonographic findings of the patellofemoral joint in patients with PFPS versus healthy individuals. Materials and Methods: The current case-control investigation was performed on 30 cases suffering from patellofemoral joint pain and 30 healthy individuals in Isfahan during 2020-21. All cases underwent ultrasonography to assess cartilage thickness, sulcus angle, and sulcus depth. We also measured the Q angle with a manual goniometer. Results: In healthy individuals, Q angle scores were statistically lower than in the cases group (P=0.002). The sulcus angle was remarkably higher among the patients compared to the controls. The cartilage thickness (P=0.88) and sulcus depth (P=0.543) scores had no statistical difference between the PFPS and healthy subjects (P<0.05). Conclusions: Patients with PFPS had significantly higher Q angle and lower sulcus angle than the healthy controls.